2008
DOI: 10.1007/s12020-008-9071-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticotropin-releasing hormone and stresscopin on vascular endothelial growth factor mRNA expression in cultured early human extravillous trophoblasts

Abstract: Corticotropin-releasing hormone (CRH) takes a role in the regulation of the onset of parturition. Stresscopin (SCP) is a high affinity ligand for CRH receptor (CRHR)-2. CRHR-2 inhibits VEGF-induced neovascularization. In the present study, we investigated the effects of CRH and SCP on VEGF expression in early placental extravillous trophoblasts (EVTs). Isolation and culture of trophoblasts differentiating into EVTs were performed by the enzymatic digestion of anchoring early placental villi. The presence of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In rat vascular smooth muscle cells (SMCs), activation of CRHR2 by Ucn 2 treatment reduces VEGF expression levels (25). In contrast, CRH increases VEGF secretion in human mast cells and VEGF mRNA levels in human extravillous trophoblasts (30,31). Our study also demonstrated that VEGF levels were decreased in the colon of CRHR1-deficient mice with colitis but increased in the colon of CRHR2-deficient mice (29).…”
Section: Vascular Endothelial Growth Factor (Vegf)supporting
confidence: 50%
See 1 more Smart Citation
“…In rat vascular smooth muscle cells (SMCs), activation of CRHR2 by Ucn 2 treatment reduces VEGF expression levels (25). In contrast, CRH increases VEGF secretion in human mast cells and VEGF mRNA levels in human extravillous trophoblasts (30,31). Our study also demonstrated that VEGF levels were decreased in the colon of CRHR1-deficient mice with colitis but increased in the colon of CRHR2-deficient mice (29).…”
Section: Vascular Endothelial Growth Factor (Vegf)supporting
confidence: 50%
“…For instance, in rat smooth muscle cells, Ucn 1 inhibited VEGF release and consequently suppressed angiogenesis (25). Moreover, either CRH or Ucn 3 decreased VEGF mRNA expression levels in cultured early placental extravillous trophoblasts and this effect was counteracted by the CRHR2 antagonist antisauvagine-30 (31). Additionally, Ucn 1 and Ucn 2 suppressed VEGF expression in hepatocellular carcinoma and small cell lung carcinoma cells via CRHR2 (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, VEGF, as an important pro-inflammatory regulator and angiogenic regulator, was found to be regulated by CRFR2. It was shown that CRF inhibited VEGF mRNA expression in cultured early placental extravillous trophoblasts through interaction with CRFR2 [40]. It was also reported that VEGF level was decreased in rat smooth muscle cells (SMCs) by UCN 1 treatment via CRFR2 [41].…”
Section: Crfr2 In Inflammationmentioning
confidence: 99%
“…The diverse placental signaling mechanisms regulated by CRH suggest that elevated CRH controls the placental “surveillance and response” system so that the fetus can detect threats to survival and adjust its developmental trajectory (6467) (Figure 2A). When stress signals (e.g., cortisol) from the maternal environment are detected by the fetoplacental unit, the “placental clock” may adapt by altering rate of synthesis of the “master” stress hormone, CRH.…”
Section: Crh–hpa Axis In Fetal Neurodevelopmentmentioning
confidence: 99%